Wpływ mistyki hiszpańskiej na duchowość karmelitanki Anny od Jezusa (Stobieńskiej) - Kaczor, Katarzyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2001)
The article deals with the 17th century autobiographic nun's characteristic vision of man as a being the relations between man and God. The 17th century was a time of rapid change all over Europe. In the 17th century arrived in Poland from Netherlands the first caramel’s nuns. There were: Anna оf the Jesus (Jadwiga Stobieńska) - the first Polish caramel’s nun, then Teresa of the Jesus (Marianna Marchocka) etc. The autobiography of Jadwiga Stobieńska’s expresses the relations between man and God, and mystical inspirations (particularly St. Teresa of Avila and St. John of the Cross). The article presents the religious direct experiences of Jadwiga Stobieńska. There are many images, motifs taken from the great tradition of religious literature. The article shows influence mysticism of St. Teresa of Avila for the Jadwiga Stobieńska’s spiritual life. This article the particularly presents the personal experiences of Polish nun (dialogue with God, the love to Him and mystical unity with God). Jadwiga Stobieńska gave original the reason of relations a man with Absolute, and shoed metaphysical and mystical the way of soul to God.